IbM INDUSTRI KULINER RUMAH TANGGA KUE KERING DI TOMPOKERSAN KOTA LUMAJANG - Adistianaya Dewa, Weda; Dwi Mumpuni, Indah; Mohammad Akhriza, Tubagus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2017)
Creative industries supported by the government one of them is the culinary industry that is currently expected not only able to increase revenue for industrial owners, but also a character of tourism in a region. Two industrial partners who became the object IbM is including the culinary industry that is precisely the cake industry. The industry is owned by Susana and Ling and is located in Lumajang District. Both partners are known to have utilized the potential to increase their production so that they can be better known in the Lumajang community by way of entrusting products in certain locations such as in the school cafeteria or market. The partner's effort to improve the variety of products also looks like a dry cake product with a selection of cheeses and corned beef and oatmeal with a selection of beans, cheeses and chocolates in which this variety is the result of partner creations. Traditional marketing methods as mentioned above also need to be improved in order to expand the product marketing network. solutions for such problems through trademark registration for partner products, enhancement of online-based marketing methods through the creation of web-based marketing applications and ongoing assistance in the form of post-grant community service cooperation as well as the procurement of more adequate means of production.